Translational Attenuation Mechanism of ErmB Induction by Erythromycin Is Dependent on Two Leader Peptides - Wang, Shasha; Jiang, Kai; Du, Xinyue; Lu, Yanli; Liao, Lijun; He, Zhiying; He, Weizhi (Frontiers in Microbiology, 2021)
Ribosome stalling on ermBL at tenth codon (Asp) is believed as major mechanisms of ermB induction by erythromycin. In this paper, we demonstrated that the mechanism of ermB induction by erythromycin depends on not only ermBL expression but also on a previously unreported ermBL2 expression. Introducing premature termination codons in ermBL, we proved N-terminal of ermBL translation is the key component for ermB induced by erythromycin while C- terminal of ermBL translation did not affect the induced expression of ermB by erythromycin. Mutation of the tenth codon (Asp10) of ermBL to other amino acids, was found that the degree of induction in vivo was not completely consistent with the data of in vitro toe printing assay. Alanine-scanning mutagenesis of ermBL demonstrated that not only N-terminal residues(R7-K11) but the latter part of ermBL(K20-K27) is even more critical for ermB induction by erythromycin. Frameshifting reporter plasmid showed there is a new leader peptide named ermBL2 exist in ermB regulatory region. Introducing premature termination mutation and Alanine-scanning mutagenesis of ermBL2 demonstrated that N-terminal of ermBL2 is essential for induction by erythromycin. The detailed function of ermBL2 needs to be further studied.